On 0-homology of categorical at zero semigroups - Polyakova, Lyudmila Yuryevna; Полякова, Людмила Юріївна (Kharkov : V. N. Karazin Kharkiv National University, 2009)
У збірнику містяться матеріали Сьомої міжнародної алгебраїчної конференції в Україні, присвяченої 120-річчю від дня народження професора Харківського університету Антона Казиміровича Сушкевича.

The collection contains the abstracts of talks of 7th International Algebraic Conference in Ukraine dedicated to the 120th anniversary of Professor of Kharkov University Anton Kazimirovich Sushkevich.
7th International Algebraic Conference in Ukraine: abstracts of talks (18-23 August, 2009, Kharkov) = 7-а Міжнародна алгебраїчна конференція в Україні: тези доповідей (18-23 серпня 2009 року, Харків) / ed. G. N. Zholtkevich. - Kharkov, 2009. - 168 р.